(3GdJLGQI hGdJfejI (B/s - (3GdShGYj, NGdO eMeOs ((3YeGf(B: s (3OGQ GdefGgL(B, s, 2006)
(3eGgjI GdJLGQI hGdJfejI, GdJLGQI GdOhdjI hGdJfejI GdGbJUGOjI, ejRGf GdeOahYGJ, eMOOGJ GdJLGQI GdNGQLjI, GdJcJdGJ GdGbJUGOjI, SjGSI GdJLGQI GdNGQLjI aj GdOhd GdfGejI, JLGQH ef GdOhd GdfGejI, efXeI GdJLGQI GdYGdejI hGdOhd GdfGejIs
(3GdeQGLY U(B.251s
Keywords: (3GdJLGQI GdNGQLjIs; (3GdJfejI GdGbJUGOjIs